2017
DOI: 10.1177/1533034617723221
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry Verification of 125I Seeds Implantation With Three-Dimensional Printing Noncoplanar Templates and CT Guidance for Paravertebral/Retroperitoneal Malignant Tumors

Abstract: Objective:To compare dose distributions of postoperative plans with preoperative plans for radioactive seed implantation of paravertebral/retroperitoneal tumors assisted by 3-dimensional printing noncoplanar templates and computed tomography.Methods:Sixteen patients with paravertebral/retroperitoneal tumors (21 lesions) underwent radioactive seed implantation with 3-dimensional printing noncoplanar templates. Prescribed dose was 110 to 160 Gy. We compared the dose distribution of the postoperative plan with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 24 publications
2
25
1
Order By: Relevance
“…In line with previous reports, the tumor volume, dose and recurrent sites might influence the effect [212324]. Encouragingly, with the improvement of technology, we were the first brachytherapy center to incorporate 3-dimensional printing template into RIS implantation, in order to increase the accuracy of treatment [252627]. Furthermore, the combination with multiple modern image technologies helped us to define the tumor margin more precisely, which might overcome the problems of target area delineation and dose coverage.…”
Section: Discussionsupporting
confidence: 72%
“…In line with previous reports, the tumor volume, dose and recurrent sites might influence the effect [212324]. Encouragingly, with the improvement of technology, we were the first brachytherapy center to incorporate 3-dimensional printing template into RIS implantation, in order to increase the accuracy of treatment [252627]. Furthermore, the combination with multiple modern image technologies helped us to define the tumor margin more precisely, which might overcome the problems of target area delineation and dose coverage.…”
Section: Discussionsupporting
confidence: 72%
“…In order to expand the indications of RSI-BT, CT-guidance technique was integrated into RSI-BT in 2002 in China, which was used to treat head and neck, thoracic, abdomen, and spinal vertebrate carcinoma [25][26][27][28][29][30]. The CTguided 125I RSI-BT was very safety and effective approach for anti-cancer treatment, especially for recurrent or metastasis carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Using 3D-printed non-coplanar templates (3D-PNCT) and CT technology, the particles can more accurately locate paravertebral/postperitoneal lesions. 35 Liu et al reported that in the treatment of recurrent high-grade gliomas, 3D-PIT based on CT/MRI fusion images can enable better positioning accuracy and dose distribution of radioactive I125 particle implantation. 36 Jiang et al studied the acute and late side effects of 3D- PNCT used in CT-guided radioactive I125 particles (RIS) implanted in recurrent cancer of the head and neck.…”
Section: Discussionmentioning
confidence: 99%